Chemical characterization of biochar and assessment of the nutrient dynamics by means of preliminary plant growth tests - Prasad, Munoo Bala Krishna; Tzortzakis, Nikos G.; McDaniel, Nicola (My University, 2018)
Biochar can be produced from several organic sources with varying nutrients and metal concentrations. Four commercial grade biochars were evaluated as peat substitute. Biochars were characterised for plant nutrients and for biological stability. The results showed that there were negligible quantities of N and P and generally high levels of K and high biological stability. When these materials were mixed with peat at 10, 25 and 50% and nutrients were added to bring them to the same level of nutrients as in fertilized peat, it was found that biochar mixtures considerably reduced the levels of calcium chloride/DTPA (CAT) extractable N (including nitrate), P, and electrical conductivity- greater extent with higher rates of biochar addition except for K. The pH and K levels were increased with biochar addition. The drop in EC has important implications regarding the use of other materials used to dilute peat, for example, composted green waste, the rate of dilution is limited due to high EC and biochar addition gives the potential for higher peat dilution of these materials. Nitrate and phosphorus are very vulnerable to leaching of these nutrients in the environment in peat substrates and the binding of these by biochar has implication for leaching and nutrient application strategy. Root development using Cress test and tomato plant height and biomass using containers, were in some cases better than peat indicating that biochar could be used to dilute peat e.g. for seedling production where root development and rapid growth are very important. Application of biochars resulted in a marked reduction of N (and P) in the plant. There were significant correlation between CAT extractable N and P and corresponding plant concentration, indicating the standard growing media test, CAT, would be suitable for assessing the nutrient status of peat biochar mixes.
Keywords: Biochar; Biological stability; CAT extractable nutrient; Nutrient dynamics; Seed germination; Tomato